Clinical Value of S-poly (T) plus Real-time PCR in Detection of Liver Cancer-related miR-199 - WU Juan; ZHANG Yaqin; WU Yunbin; CHEN Min; YU Zhou; CAO Yingping (Zhongliu Fangzhi Yanjiu, 2020)
Objective To explore the advantages and disadvantages of S-poly(T) plus qRT-PCR and Poly (A) qRT-PCR methods in detecting peripheral blood serum miR-199. Methods S-poly(T) plus RT-PCR and Poly(A) qRT-PCR methods were used to detect the serum miR-199 in patients with liver cancer and healthy controls in three aspects of sensitivity, linearity and repeatability to evaluate their potential clinical value. Results The Ct values of S-poly(T) plus qRT-PCR method for miR-199 in healthy controls was significantly lower than that of Poly(A) qRT-PCR method (P < 0.0001); and the S-poly(T) plus qRT-PCR method had better linear correlation (P=0.0027) and repeatability (P=0.010). S-poly(T) plus qRT-PCR method had better sensitivity in detecting serum miR-199 in liver cancer patients comparing with Poly (A) qRT-PCR method. Conclusion In the detection of liver cancer serum miR-199, S-poly(T) plus qRT-PCR method is more sensitive, repeatable and stable than Poly(A) qRT-PCR.